Train Control System Formalization Modeling oriented Movement Authority - Shuxu Zhao; Xiaoming Wang (Institute of Advanced Engineering and Science, 2012)
Chinese Train Control System-3(CTCS-3) was integrated via various control system devices, assurance of CTCS-3 system transmission probability relied on empirical judgment, it is necessary to form its formalization to support integration for system stability of the whole CTCS-3. Movement Authority(MA) acts on the whole information process of CTCS-3 to control train, its process properties can be as the reflection of CTCS probability. Aiming at that, paper selected MA as the objective, proposed MA-oriented CTCS-3 formalization modeling. Paper designed generation and transmission algorithms of MA, formed MA computation models for application functions. Based on computation models, paper constructed MA hierarchical Colored Petri Nets(CPN) models, and completed MA timed CPN model, the report and experimental result demonstrate that the model proposed is effective and can reflect CTCS-3 system properties accurately. DOI: http://dx.doi.org/10.11591/telkomnika.v10i5.1352